If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 4) + -15 = 18 + 2 Reorder the terms: -7(4 + x) + -15 = 18 + 2 (4 * -7 + x * -7) + -15 = 18 + 2 (-28 + -7x) + -15 = 18 + 2 Reorder the terms: -28 + -15 + -7x = 18 + 2 Combine like terms: -28 + -15 = -43 -43 + -7x = 18 + 2 Combine like terms: 18 + 2 = 20 -43 + -7x = 20 Solving -43 + -7x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '43' to each side of the equation. -43 + 43 + -7x = 20 + 43 Combine like terms: -43 + 43 = 0 0 + -7x = 20 + 43 -7x = 20 + 43 Combine like terms: 20 + 43 = 63 -7x = 63 Divide each side by '-7'. x = -9 Simplifying x = -9
| 4x+5=-16 | | 2x=3z+12y | | 5(8y-6)=10y | | 3x(x-1)=12 | | 2x(x-1)=12 | | 5-4b=3+b | | 2x=3z*12y | | 2x=3z+12 | | 43y=6(7y-5) | | 2x=3z*12 | | 2x=3*12 | | =x^2+10x+21 | | 5x-35=15 | | -7-6=4x+4-3x | | x^2-17x=11 | | 2x^2-5=-3x | | 100=0 | | 15+0.5=25+0.25 | | 3x+5=4x-9 | | 8x+16=26-2x | | -3x-3x=60-6 | | x^2-17x-11=0 | | 6x=72-6x | | 2x+18=58-2x | | 5+2m=-m-1 | | -14=2g | | 3x=70-7x | | 3x=70.7x | | t^2-2t+16=0 | | 2x=12-4x | | h^2+4h-60=0 | | 6b+13=2b-11 |